Hydrogen Sulfide Promotes Nodulation and Nitrogen Fixation in Soybean–Rhizobia Symbiotic System - Zou, Hang; Zhang, Ni-Na; Pan, Qing; Zhang, Jian-Hua; Chen, Juan; Wei, Ge-Hong (Molecular plant-microbe interactions, 2019)
The rhizobium–legume symbiotic system is crucial for nitrogen cycle balance in agriculture. Hydrogen sulfide (H 2 S), a gaseous signaling molecule, may regulate various physiological processes in plants. However, whether H 2 S has regulatory effect in this symbiotic system remains unknown. Herein, we investigated the possible role of H 2 S in the symbiosis between soybean (Glycine max) and rhizobium (Sinorhizobium fredii). Our results demonstrated that an exogenous H 2 S donor (sodium hydrosulfide [NaHS]) treatment promoted soybean growth, nodulation, and nitrogenase (Nase) activity. Western blotting analysis revealed that the abundance of Nase component nifH was increased by NaHS treatment in nodules. Quantitative real-time polymerase chain reaction data showed that NaHS treatment upregulated the expressions of symbiosis-related genes nodA, nodC, and nodD of S. fredii. In addition, expression of soybean nodulation marker genes, including early nodulin 40 (GmENOD40), ERF required for nodulation (GmERN), nodulation signaling pathway 2b (GmNSP2b), and nodulation inception genes (GmNIN1a, GmNIN2a, and GmNIN2b), were upregulated. Moreover, the expressions of glutamate synthase (GmGOGAT), asparagine synthase (GmAS), nitrite reductase (GmNiR), ammonia transporter (GmSAT1), leghemoglobin (GmLb), and nifH involved in nitrogen metabolism were upregulated in NaHS-treated soybean roots and nodules. Together, our results suggested that H 2 S may act as a positive signaling molecule in the soybean–rhizobia symbiotic system and enhance the system’s nitrogen fixation ability.